Eksplorasi Persepsi Ibu Terhadap Kebiasaan Makan Anak Dengan Stunting Pada Masyarakat Suku Banjar: Studi Etnografi - Filia Sofiani Ikasari; Iis Pusparina; Ahmad Rizqo Abdillah (Faculty of Nursing, Universitas Pelita Harapan, 2025)
Stunting remains a major public health issue in Banjar Regency, especially among the Banjar ethnic community living along riverbanks. Poor child feeding habits, shaped by cultural, social, and economic factors, are key contributors. This study aims to explore mothers’ perceptions of child-feeding practices within the cultural context of the Banjar community. A qualitative ethnographic approach was employed. Data were collected through in-depth interviews with 17 Banjar mothers of children with stunting, selected using purposive sampling. Data analysis involved transcription, categorization, and thematic analysis using NVivo 12. The study identified five main themes: child dietary patterns, children’s mealtime behaviors, maternal expectations, household food decision-makers, and maternal perceptions of healthy food. The findings indicate that both maternal and child-related factors significantly shape children’s eating habits. Culturally sensitive stunting interventions that actively involve mothers and household decision-makers are therefore recommended.